Enhancement of London Dispersion in Frustrated Lewis Pairs: Towards a Crystalline Encounter Complex - Holtrop, Flip; Helling, Christoph; Lutz, Martin; van Leest, Nicolaas P.; de Bruin, Bas; Slootweg, J. Chris (Synlett, 2022)
The encounter complex, i.e., the pre-organized assembly consisting of a Lewis acid and a Lewis base, is a fundamental concept in frustrated Lewis pair (FLP) chemistry. However, this donor–acceptor complex is challenging to study due to its transient nature. Here, we present a combined theoretical and experimental investigation on the potential isolation of an encounter complex enabled by enhancement of London dispersion forces between a sterically encumbered Lewis acid and base pair. Guided by computational analyses, the FLP originating from the bulky triarylamine N(3,5-tBu2C6H3)3 and the novel triarylborane B(3,5-tBu2C6H3)3 was investigated, leading to the isolation of a 1:1 co-crystal of both FLP components.
Keywords: frustrated Lewis pairs; encounter complex; London dispersion forces; Lewis acid; Lewis base